Effects on accidents of police checks of drivers of heavy goods vehicles in Norway - Rune Elvik; Live Tanum Pasnin; Tor-Olav Nævestad (Transportation Research Interdisciplinary Perspectives, 2022)
During the period from 2007 to 2019, the number of drivers of heavy goods vehicles checked by the traffic police in Norway varied substantially. It declined during the first years of the period, then increased. This paper studies where there is an association between these variations and annual changes in the number of accidents involving heavy goods vehicles. A negative relationship is found: the more drivers checked, the fewer accidents. The relationship can be described by means of a dose–response function. The function indicates that when the number of drivers checked by the police is reduced by 50%, one may expect the number of accidents involving heavy goods vehicles to increase by 7.5%. A 50% increase in the number of drivers checked will be associated with a 3.5% reduction in the number of accidents, and a 150% increase in the number of drivers checked will be associated with an 8.6% reduction in the number of accidents.